Management New Edition Available - Neck, Christopher P. (SAGE Publications, Inc. (US), 2020)
Management, Third Edition introduces students to the planning, organizing, leading, and controlling functions of management with an emphasis on how managers can cultivate an entrepreneurial mindset. The text includes 34 cases profiling a wide range of companies including Lululemon, Nintendo, Netflix, Trader Joe’s, and the NBA. Authors Christopher P. Neck, Jeffrey D. Houghton, and Emma L. Murray use a variety of examples, applications, and insights from real-world managers to help students develop the knowledge, mindset, and skills they need to succeed in today’s fast-paced, dynamic workplace. This title is accompanied by a complete teaching and learning package.